TECHNICAL PROGRESS AND ITS FACTORS IN RUSSIA’S ECONOMY - Simon, Jr, György (Economic Annals, 2010)
In this paper long-term growth in Russia’s economy is viewed in the context of technical progress, based on both neoclassical and endogenous theories. The dynamics of economic growth with some aspects of catch-up development are examined, as well as capital deepening. TFP is quantified in terms of both output and productivity increases to reveal the leading role of embodied technical progress in productivity growth. An endogenous growth model helped to discern three complex factors of technical progress in the Russian economy, to which at the macro level a factor related to natural wealth (oil and gas resources) was added. This enabled the author to conclude that the most important macroeconomic factor of Russia’s technical progress in the half century from the early 1960s to the late 2000s was its immobile component. At the manufacturing level the situation was more complicated, as the initial leadership of creative technical progress was superseded by the dominance of the mobile factor. The collapse of the Soviet Union made the Russian economy more service-oriented and radically changed the conditions of economic modernisation, in which technology transfer ensured by FDI began to play a more prominent part, particularly after the default of 1998.